Forged : a novel - Teller, Danielle (Pegasus Books, 2025)
"In the Gilded Age, a time of abject poverty and obscene wealth, a desperate and ambitious young woman strikes out for a new life in the rising industrial cities of America. Naive Fanny is thrust into a Darwinian world where she is cast out and preyed upon, but she's a survivor and quickly learns from her struggles. Thanks to her close observations of the mercenary actors around her, Fanny discovers the power of illusion and how it can overcome the immutability of social class and the ruthless rules of capitalism. Shedding her past, Fanny embarks on a darkly thrilling transformation. She becomes Kitty Warren--a forger, con artist, and thief. Exploiting the greed and self-regard of the powerful, Kitty builds her own castle in the sky, yet she finds real pleasure and fulfilment elusive, and soon her foundations start to crumble"--Amazon.com.